2018
DOI: 10.1007/s13312-018-1417-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fluid Overload with Mortality in Critically-ill Mechanically Ventilated Children

Abstract: Objectives: To study the association of fluid overload with mortality and morbidity in critically-ill mechanically ventilated children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A study of mortality-related factors in CRRT for AKI also confirmed that MV, the use of vasoactive drugs and other factors were related to increased mortality [ 28 ]. It is also worth noting that in a study on FO and mortality in 118 children with MV [ 29 ], there was a significant correlation between FO and organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A study of mortality-related factors in CRRT for AKI also confirmed that MV, the use of vasoactive drugs and other factors were related to increased mortality [ 28 ]. It is also worth noting that in a study on FO and mortality in 118 children with MV [ 29 ], there was a significant correlation between FO and organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Once the treatment of children with cancer involves the administration of large amounts of volume through the use of antimicrobials, hyperhydration, sedatives, chemotherapy, and transfusions, these patients show a higher risk of volume overload, especially in the presence of AKI with reduced urine flow rate. [25,26] Patients with positive cumulative fluid balance show longer mechanical ventilation time and greater need for RRT. [27] Raymakers-Janssen et al (2019) [28] observed in their multicentric study with pediatric cancer patients that fluid overload (p=0.003) and a need for inotropic support at the beginning of the continuous renal replacement therapy (p=0.004) are independent predictors of death.…”
Section: Discussionmentioning
confidence: 99%
“…However, in children who are critically ill and on mechanical ventilation, it is linked to poor organ function, a longer time spent in the PICU, and a longer duration of mechanical ventilation. 13 Another prospective study demonstrated that 64 (17.3%) of the patients experienced early fluid overload within the first 24 hours of hospitalization. The PICU mortality rate of the overall group was 4.9%.…”
Section: Evidence From Literature For Adverse Effects Of Fluid Overloadmentioning
confidence: 99%